A novel technology to manufacture biodegradable polylactide bead foam products. (15th October 2015) - Nofar, Mohammadreza; Ameli, Aboutaleb; Park, Chul B.
Graphical abstract: Highlights: A new route to manufacture expanded polylactide (EPLA) bead foams is developed. EPLA bead foams are produced by generating double crystal melting peak structure. Generation of double crystal peak significantly improves PLA's foaming properties. Generation of double crystal peak creates strong intra-bead sintering among beads. Abstract: Bead foaming technology with double crystal melting peak structure has been recognized as a promising method to produce high-performance low-density foams with complex geometries. Polylactide (PLA) bead foaming has been of the great interest of researchers due to its origin from renewal resources and biodegradability. However, due to the PLA's low melt strength and slow crystallization kinetics, the attempts have been limited to the manufacturing methods used for expanded polystyrene (EPS). In this study, we developed microcellular PLA bead foams with double crystal melting peak structure in a large content using a lab-scale autoclave system followed by molding of the beads. PLA bead foams were produced with expansion ratios and average cell sizes ranging from 6 to 31-fold and 6 to 50 μm, respectively. The high-melting point crystals generated during gas-saturation significantly affected the expansion ratio and cell density of the PLA bead foams by enhancing the PLA's melt strength and promoting cell nucleation around the crystals. The tensile properties of the molded EPLA bead foams showed that EPLA bead foams with double crystal melting peak can be a promising substitute not only for EPS but also for expanded polypropylene (EPP) bead foams.